The Visible World Samuel van Hoogstraten's Art Theory and the Legitimation of Painting in the Dutch Golden Age - Weststeijn, Thijs (Amsterdamse Gouden Eeuw Reeks, 2008)
How did painters and their public speak about art in Rembrandt's age? This book about the writings of the painter-poet Samuel van Hoogstraten, one of Rembrandt's pupils, examines a wide variety of themes from painting practice and theory from the Dutch Golden Age. It addresses the contested issue of 'Dutch realism' and its hidden symbolism, as well as Rembrandt's concern with representing emotions in order to involve the spectator. Diverse aspects of imitation and illusion come to the fore, such as the theory behind sketchy or 'rough' brushwork and the active role played by the viewer's imagination. Taking as its starting point discussions in Rembrandt's studio, this unique study provides an ambitious overview of Dutch artists' ideas on painting.